The Effect of Using Inclusion Style According to Feed back timing on Learning and Retention Diving Skill in Artistic Gymnastic for men - Saleh, Ayad (Journal of Physical Education, 2010)
The aim of the study to identifying the effect of using inclusion style According to Feed back timing on Learning and Retention Diving Skills in Artistic Gymnastic for men ,and to investigate which style best between groups three whose using in experimental study .(inclusion style according to immediate feed back , inclusion style according to late feed back , the normal style ) in learning and retention diving skill in artistic Gymnastic for men. The researcher used the experimental method consist subject were chosen from the department of health and fanning / College of Physical Education , the researcher used the (spss) to treatment results which find it that(mean ,standard deviation, T.test, F test ,LSD test, law of retention ) The researcher concluded each of three styles proved the good effects in learning and retention diving skill in artistic Gymnastic for men ,but effects ratios distinctness between styles